Heterologous Expression and Biochemical Characterization of a New α-Amylase from Nocardiopsis aegyptia HDN19-252 of Antarctic Animal Origin - Fuhao Liu; Xiangnan Zheng; Wenhui Liao; Xingtao Ren; Chuanteng Ma; Guojian Zhang; Qian Che; Tianjiao Zhu; Wenxue Wang; Tao Zhang; Feng Han; Dehai Li (Marine Drugs)
α-Amylases, catalyzing starch degradation, serve as vital biocatalysts in industrial and pharmaceutical applications. This study identified a new α-amylase, Alphaz, from Nocardiopsis aegyptia HDN19-252 of Antarctic animal origin, achieving heterologous expression in Escherichia coli. Phylogenetic analysis confirmed its classification into the GH13_5 subfamily of glycoside hydrolases. Recombinant Alphaz exhibited optimal activity at 40 °C/pH 8.0 while maintaining stability across 0–30 °C and pH 6.6–9.6. Its distinctive halotolerant properties included full activity retention in 0.6 M NaCl and >60% efficiency in salt-free conditions. The enzyme exhibits tolerance to K+, Ca2+, and Fe³+ while demonstrating specific inhibition by Cu2+/Zn2+. With its heterologously validated functional properties, Alphaz emerges as a programmable enzymatic tool offering advantages in sustained-release formulation quality control, targeted prodrug modification, and precision medicine applications, thereby enabling sustainable biomanufacturing solutions that harmonize process reliability with environmental compatibility.